THE EFFECTIVENESS OF SHADOWING METHOD FOR IMPROVING SPEAKING SKILLS IN FOREIGN LANGUAGE EDUCATION - Talapova A.K.; Iliyas Zh.N. (World Scientific Reports, 2024)
The shadowing method, a practice where learners listen to and simultaneously repeat spoken language, has gained recognition for its potential to enhance speaking skills in foreign language education. This study investigates the effectiveness of shadowing in improving pronunciation, fluency, intonation, and overall speaking proficiency among intermediate and advanced learners. Using a mixed-methods approach, the research combines quantitative pre- and post-test assessments with qualitative insights from journals and interviews. Participants reported increased confidence and motivation, though challenges such as the fast pace of recordings and unfamiliar accents were noted. Tailored materials, extended practice duration, and feedback mechanisms were identified as critical for optimizing shadowing’s benefits. These findings affirm the shadowing method as an engaging and effective tool for foreign language learning, while also highlighting areas for refinement to address diverse learner needs.